The re-emergence of The Forty Martyrs of Sebaste in the church of Saint Peter and Paul, Famagusta, Northern Cyprus - Walsh, Michael (Elsevier France-Editions Scientifiques Medicales Elsevier, 2007)
This article presents the first study of a painting, possibly the Forty Martyrs of Sebaste, which has been concealed for over 500 years, and which has, this century only, re-emerged through plaster removal in the church of SS. Peter and Paul in Famagusta, N. Cyprus. Though very badly damaged the painting, which has remained undocumented and unstudied in the history and art history of Cyprus, may offer vital clues concerning internationalism and cultural interaction in Cyprus in the 14th and 15th centuries. It also offers specialists a rare glimpse at Italian ecclesiastical wall painting from this rich period in western art history, and makes clear the intellectual loss that might be felt if some basic conservation processes are not begun soon. Lastly, in the light of the changing political situation in that island it invites scholarship in a range of disciplines to the church and to other historic landmarks within the old city walls. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: Cyprus; gothic; Lusignan; Famagusta; medieval; enlart; SS. Peter and Paul; conservation; restoration; Martyrs of Sebaste